Synthesis and Modification of Nano-Precipitated Calcium Carbonate (PCC) with Addition of Ethylene Glycol - Sani; Mega Rosilina; Mochamad Titus Maulana; A. R Yelvia Sunarti; Srie Muljani; Dwi Hery Astuti; Isni Utami (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2022)
ZA fertilizer waste (Ammonium sulfate) is waste generated from the industrial process of producing ZA fertilizer. The waste contains very high calcium and has the potential to be used as a raw material in the manufacture of Precipitated Calcium Carbonate (PCC). PCC with certain qualities can be developed in the field of advanced materials, with size modification into nanoparticles. One method to produce nanoparticles is using the coprecipitation method, with the help of a polymer solution. This study aims to produce Nano-PCC by finding the best conditions of CaCl2: Ethylene Glycol mole ratio and stirring speed. Nano-PCC is synthesized by reacting fertilizer waste with HCl to form a CaCl2 solution. Then, the solution is mixed with ethylene glycol to prevent particle agglomeration so that the size obtained will be smaller. The mixture is then reacted with Na2CO3 to form precipitated calcium carbonate (PCC). In this study, the variables were the mole ratio of CaCl2: ethylene glycol (1:12, 1:14, 1:18, 1:20) and stirring speed (350, 500, 650, 800, and 950 rpm). Based on PSA analysis, the Nano-PCC obtained at the smallest CaCl2: ethylene glycol ratio 1:12, stirring speed 950 rpm was 51.83 nm. Based on Scherrer’s calculations with XRD, the particle size obtained was 48.25 nm. SEM analysis showed that the crystals formed were dominated by vaterite crystals, with a size range of 55.71-607.79 nm.